Nanocrystalline/Nanosized Ni1−γFe2+γO4 Ferrite Obtained by Contamination with Fe During Milling of NiO–Fe2O3 Mixture. Structural and Magnetic Characterization. Issue 2 (26th October 2012) - Marinca, Traian F.; Chicinaş, Ionel; Isnard, Olivier; Popescu, Violeta; Johnson, D.
<x xml:space="preserve">Abstract</x> The nanocrystalline nickel ferrite (NiFe2O4) was synthesized by reactive milling starting from equimolar mixture of oxides. The iron contamination during milling leads to a solid state reaction between Fe and NiFe2O4 spinel. This reaction starts for a milling time longer than 30 h. A mixed nickel–iron ferrite (Ni1−γFe2+γO4) and elemental Ni are obtained. The evolution of the nickel–iron mixed ferrite during milling and its properties were investigated using X‐ray diffraction, Fourier Transform Infrared Spectroscopy (FTIR), Laser Particles Size Analyzer and magnetic measurements. Annealing treatment (350°C/4 h in vacuum) is favorable to the reaction between phases. Replacement of Ni2+ cations by iron cations provided by contamination leads to the increase of lattice parameter value of the spinel structure. The magnetization of the nickel–iron mixed ferrite newly formed is larger than the nickel ferrite magnetization (13.6 μB/f.u. and 6.22 μB/f.u., respectively), due to the magnetic moment of Fe2+ cation which is double as compared to the Ni2+ cation. Magnetization of the milled samples decreases during milling due to the structural changes induced by milling in the nickel–iron mixed ferrite. The annealing induces a reordering of the cations which leads to a larger magnetization.